Structural performance of steel reinforced concrete T-shaped columns exposure to high temperature. (December 2021) - Zhang, Bingjie; Wang, Yuzhuo; Li, Guoqiang; Qu, Shuang; Fu, Chuanguo; Xu, Tiangui
Abstract: This paper mainly focused on the mechanical properties of steel reinforced concrete (SRC) T-shaped columns subjected to axial compression in high temperature. A test program consisting of 8 SRC T-shaped columns was carried out at different influence of specimen parameters. The investigated parameters included axial load ratio, loading eccentricity, loading angle, stirrup spacing and steel ratio. The test results showed that: (1) The failure of axial compression specimens was mainly compression failure. However, the failure of eccentric compression specimens became flexural failure due to the loading eccentricity and loading angle. (2) The fire resistance decreased 50.8% with increasing axial load ratio from 0.2 to 0.6. Decreasing steel ratio from 6.9% to 6.0% led to a decline of 39.4% in the fire resistance. The fire resistance of specimens varied only 1.2% for stirrup spacing from 200 mm to 300 mm. (3) The fire resistance of eccentric compression specimens decreased 8.8%～46.2% compared with the axial compression specimens. The fire resistance of specimens decreased 12.9% with the increase of loading eccentricity from 0 to 40 mm. The fire resistance of specimens decreased 46.2% with the increase of loading angle from 0° to 90°. (4) The influence of axial load ratio and loading angle on the fire resistance was much greater than loading eccentricity. Finally, the fire resistance model of specimens in fire was proposed, and the spatial distribution of fire resistance under the action of two factors was presented, which provided a reference for the post-fire assessment of SRC columns.